2001
DOI: 10.1093/treephys/21.12-13.869
|View full text |Cite
|
Sign up to set email alerts
|

Link between diurnal stem radius changes and tree water relations

Abstract: Internal water reserves are depleted and replenished daily, not only in succulent plants, but also in trees. The significance of these changes in tissue water storage for tree water relations was investigated by monitoring diurnal fluctuations in stem radius. In 6-year-old potted Norway spruce (Picea abies (L.) Karst.) trees, whole-tree transpiration rate (T), sap flow at the stem base and fluctuations in stem radius were measured at 10-min intervals over eight successive weeks. The dynamics of diurnal water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
186
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(218 citation statements)
references
References 24 publications
18
186
1
3
Order By: Relevance
“…The maximum contribution of the storage water to daily transpiration varied between 28 and 45%. These values fall within the wide range of values that can be found in the literature: ranging from 1 up to 50% (Čermák et al, 2007) or even up to 65% (Zweifel et al, 2001). -s t o r a g e w a t e r u s e S t o r a g e w a t e r f l o w ( k g h -1 ) V P D ( k P a ) + s t o r a g e w a t e r r e c h a r g e …”
Section: Variability Of Storage Water Usesupporting
confidence: 80%
See 2 more Smart Citations
“…The maximum contribution of the storage water to daily transpiration varied between 28 and 45%. These values fall within the wide range of values that can be found in the literature: ranging from 1 up to 50% (Čermák et al, 2007) or even up to 65% (Zweifel et al, 2001). -s t o r a g e w a t e r u s e S t o r a g e w a t e r f l o w ( k g h -1 ) V P D ( k P a ) + s t o r a g e w a t e r r e c h a r g e …”
Section: Variability Of Storage Water Usesupporting
confidence: 80%
“…Nonetheless, storage water contributes substantially to daily transpiration, irrespective of the climatic conditions. These results confirm that stored water plays an important role not only during periods of drought, but whenever water transport occurs within the tree (Zweifel et al, 2001). These last mentioned authors found that even in well-watered soils the tree water reserves were depleted every morning.…”
Section: Effects Of Vapour Pressure Deficitsupporting
confidence: 76%
See 1 more Smart Citation
“…A T vs. SF lag was discussed (Cruiziat et al 2002) but not frequently tested, presumably due to the differentiation between studies using gas (T) and liquid phase (SF) measurement techniques. Two notable exceptions are Zweifel et al (2001) and Fisher et al (2007), who showed time lags between T and SF of 0.5-3 hr. Comparing SF rates at the bottom and high crown of large tropical trees, Meinzer et al (2003) found up to a 2 hr lag time.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing SF rates at the bottom and high crown of large tropical trees, Meinzer et al (2003) found up to a 2 hr lag time. The role of tree water storage was shown in many studies (Zweifel et al 2001, Meinzer et al 2003, McLaughlin et al 2003, Fisher et al 2007, Meinzer et al 2009), some showing a major storage contribu-tion, e.g., 10-75% of daily T in potted, young Norway spruce (Picea abies -Zweifel et al 2001), or a more minor contribution of 2-10% in adult yellow poplar (Lirodendron tulipifera -McLaughlin et al 2003) and down to zero stem storage in the woody monocot Bamboo suffering from cavitation (Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%